Chamomile cultivation - Step towards rural prosperity - Kumar, Dipender; Suryavanshi, Priyanka; Chauhan, Amit (Indian Horticulture, 2021)
There is good potential for chamomile cultivation as commercial crop in India. Since it is a valuable crop for aroma industries and has high export value, it is necessary to promote this crop among small and marginal farmers, to secure their livelihood. CSIR-CIMAP with all other leading scientific institution is working hard to increase its area, its inclusion in existing cropping systems and adoption on large scale for bringing rural prosperity and self reliant India.